Stakeholder perspectives on digital wellbeing in Saudi Arabia: a cross-sectional survey - Saud Abdulaziz Alomairah; Michelle Colder Carras; Dahlia Aljuboori; Juliann Saquib; Nazmus Saquib; Mayank Date; Kyeongwon Kim; Faisal Aldayel; Michelle R. Kaufman; Laura K. Clary; Vincent G. van der Rijst; Anouk Tuijnman; et al. (BMC Public Health)
Abstract Background In Saudi Arabia, the rapid growth of digital media and smartphone use has raised concerns about problematic usage and its impacts on well-being, especially among young people. Research on stakeholder perspectives regarding intervention strategies remains limited. Objective This study aimed to gather insights from societal stakeholders, including youth, parents, policymakers, industry leaders, clinicians, educators, and digital media users, to inform culturally tailored interventions for digital well-being in Saudi Arabia. Methods A purposeful non-random sample of 92 participants representing different stakeholder groups was recruited to complete an online survey, answering questions about their experiences and perspectives on digital media use. Primary stakeholder group was assigned based on participant self-selection. We analyzed distributions of categorical variables related to media use time, reasons for use, impacts, self-regulation strategies, and perceived effectiveness of interventions (e.g., education programs, media campaigns, Internet use restrictions). Results Of the participants, 63.0% were male, and 46.7% were under 25 years old. Regular digital media users, individuals with problematic Internet use, and clinicians/health professionals comprised 26.1%, 18.5%, and 18.5% of respondents, respectively. Extensive screen time was common, with 47.8% reporting four or more hours of recreational digital use on weekdays and 56.6% on weekends. Participants reported both positive impacts (e.g., social connections, school/work performance) and negative impacts (e.g., sleep disruption, reduced physical activity) of digital media use. Efforts to regulate media use were reported by 72.8%, with strategies like deleting apps or digital detoxes. At least 50.0% of participants endorsed all proposed intervention approaches as likely effective for improving digital well-being, with educational programs for parents, school programs, and regulatory apps receiving over 75.0% support. Children and adolescents were seen as key target groups for these interventions. Conclusions Findings from this diverse stakeholder sample suggest that digital well-being interventions in Saudi Arabia should prioritize youth, focusing on education-based approaches and apps for media regulation. Incorporating these perspectives can lead to culturally relevant interventions addressing the unique challenges of digital media use in Saudi Arabia. The generalizability of the findings may be limited due to sample size and potential overrepresentation of certain stakeholder groups.